Variability of Air Masses Over Podlasie (Ne Poland) in the Years 2001–2010 - Kierklo, Karolina (Bulletin of Geography. Physical Geography Series, 2012)
This paper concerns the frequency and duration of air masses over Podlasie (NE Poland) in the years 2001-2010. The synoptic maps in the Daily Meteorological Bulletin of the Institute of Meteorology and Water Management (IMGW 2001-2010) were the basis for the designation of six air masses observed over the area of Podlasie every day for 12.00 UTC. They were: arctic air (A), continental polar air (cP) partly transformed from old arctic air (oA), maritime polar air (mP), maritime warm polar air (mwP), old maritime polar air (omP), tropical air (T). The analysis shows that the most frequent air mass in the whole period was cP partly transformed from oA (approx. 33%) followed by omP (approx. 24%) and mP (19%). Tropical air occurred over Podlasie with the lowest frequency, with a value of only 3.6%. The frequencies of their occurrence varied from year to year. Less than 12% of cases (approx. 210) occurred for 4-20 days. The minimum values occurred for periods of more than 9 days (cP and omP masses, only). Slightly higher values occurred in the case of 7- to 9-day periods (6-14 cases 1.5%).